2021
DOI: 10.1186/s13046-021-01976-w
|View full text |Cite
|
Sign up to set email alerts
|

CircPVT1 promotes proliferation of lung squamous cell carcinoma by binding to miR-30d/e

Abstract: Background Circular RNAs (circRNAs) are a new type of extensive non-coding RNAs that regulate the activation and progression of different human diseases, including cancer. However, information on the underlying mechanisms and clinical significance of circRNAs in lung squamous cell carcinoma (LUSC) remains scant. Methods The expression profile of RNAs in 8 LUSC tissues, and 9 healthy lung tissues were assayed using RNA sequencing (RNA-seq) technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…Recent study of Huang M. and colleagues showed that circPVT1 is upregulated in cell upon irradiation treatment highlighting that silencing of circPVT1 enhances NSCLC cell sensitivity response by acting as a sponge for miRNA-1208 [ 96 ]. Recent study of Shi J. and colleagues, demonstrated that circPVT1 promotes the tumorigenic phenotype in lung squamous cell carcinoma by sequestering miR-30d and miR-30e thus upregulating their target CCNF (Chromatin Condensation and Nuclear Fragmentation), the substrate recognition subunit of SCF ubiquitin ligase complexes which has a pivotal role in cancer since it is able to sustain cell proliferation [ 61 ]. Another study of Danac J. M. C. and colleagues showed that circPVT1 upregulates NRAS (Neuroblastoma RAS viral oncogene homolog) by acting as a miRNA sponge on let-7 thus sustaining the oncogenic phenotype [ 62 ].…”
Section: The Circpvt1/lncpvt1/c-myc Oncogenic Networkmentioning
confidence: 99%
“…Recent study of Huang M. and colleagues showed that circPVT1 is upregulated in cell upon irradiation treatment highlighting that silencing of circPVT1 enhances NSCLC cell sensitivity response by acting as a sponge for miRNA-1208 [ 96 ]. Recent study of Shi J. and colleagues, demonstrated that circPVT1 promotes the tumorigenic phenotype in lung squamous cell carcinoma by sequestering miR-30d and miR-30e thus upregulating their target CCNF (Chromatin Condensation and Nuclear Fragmentation), the substrate recognition subunit of SCF ubiquitin ligase complexes which has a pivotal role in cancer since it is able to sustain cell proliferation [ 61 ]. Another study of Danac J. M. C. and colleagues showed that circPVT1 upregulates NRAS (Neuroblastoma RAS viral oncogene homolog) by acting as a miRNA sponge on let-7 thus sustaining the oncogenic phenotype [ 62 ].…”
Section: The Circpvt1/lncpvt1/c-myc Oncogenic Networkmentioning
confidence: 99%
“…Finally, Shi et al. [ 237 ] revealed that circPVT1 was significantly upregulated in the tissues, serum, and cell lines of patients with LSCC and promoted LSCC progression by increasing cyclin F expression, acting as a sponge for miR-30d and miR-30e.…”
Section: Circular Rna Pvt1 In Various Human Tumorsmentioning
confidence: 99%
“…Most available literature regarding research on circRNAs and lung cancer seems to be from studies published in Asia. To avoid differences between races, the present review uniformly selected studies with Asian patients (23,39,62,83,85,87,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106). Almost all circRNAs and tumor prognoses were associated with TNM stage and lymph node metastasis in the 20 groups of circRNAs listed in the table.…”
Section: Circrnas and The Prognosis Of Patients With Lung Cancermentioning
confidence: 99%
“…In the 40th month, the survival rate of the high expression group was only 50%, while the low expression group had a higher rate of ~90%. Shi et al ( 84 ) reported that patients with lung squamous cell carcinoma (LUSC) who expressed high levels of circ_PVT1 had a lower overall survival (OS) than patients with LUSC who expressed low levels of circ_PVT1. Multivariate analysis confirmed that circ_PVT1 expression is a potential independent predictor of OS.…”
Section: Circrnas and The Prognosis Of Patients With Lung Cancermentioning
confidence: 99%